Foucault a-t-il cru à ses doctrines ? Foucault contre le foucaldisme - Cseke, Ákos (Verbum – Analecta Neolatina, 2017)
This paper examines two fascinating but at the same time problematic “uses” of the philosophy of the late Michel Foucault. One of them is what Paul Veyne refers to as the question of origin (the origin of history and of historical events); the other, originating in the book entitled Use of Bodies by Giorgio Agamben, is the issue of subjectivity. It seems that in his philosophical research of the eighties which he calls “the courage of truth”, Foucault was hardly interested in the philosophical doctrines that he had developed previously. I argue that Foucault’s main target – “thinking differently” – was not only a slogan that he invented for himself, it was a real profession of faith: philosophy was considered by him as an act that allowed him to unlearn his own convictions, methods, theories and truths of yesteryear.